Association of pre-exiting heart failure with long-term mortality and the recurrence of sepsis - Jin-Wen Zhu; Xiu-Ping Hu; Jun Jin; Bai Xu; Run Zhang; Sen Ye; Fang-Xiao Gong; Jun Hong; Qian Li; Xiang-Hong Yang; Ren-Hua Sun (Scientific Reports)
Abstract This retrospective cohort study aimed to evaluate the association between pre-existing heart failure and both mortality and the recurrence of sepsis. A total of 16,092 sepsis patients without a history of heart failure and 841 sepsis patients with pre-existing heart failure were identified from the Medical Information Mart for Intensive Care version IV (MIMIC-IV ) database. All patients were adults admitted to intensive care units, and no specific interventions were applied. After matching, Kaplan–Meier survival analysis showed significantly poorer long-term survival rates in patients with heart failure, both in the original (p < 0.0001) and the matched cohort (p = 0.00059). Mortality rates were tracked over different time periods, revealing that the mortality disparity became evident after the first year (p = 0.029). Besides, the cumulative incidence of sepsis recurrence was substantially higher in patients with a history of heart failure (p < 0.001) when deaths without recurrence were treated as competing events. Moreover, there was no statistically significant difference observed in the deaths without recurrence between the two groups (p = 0.251). In conclusion, pre-existing heart failure is associated with an increased risk of long-term mortality, which may be partly explained by a higher incidence of recurrent sepsis in this population.